Anxiety in Cancer Patients during 18F-FDG PET/CT Low Dose: A Comparison of Anxiety Levels before and after Imaging Studies. (14th March 2017) - Grilo, Ana; Vieira, Lina; Carolino, Elisabete; Oliveira, Cátia; Pacheco, Carolina; Castro, Maria; Alonso, Juan
Abstract : Objective . Assessing the level of anxiety in oncology patients who underwent 18 F-FDG PET/CT low dose scan and identifying the main reasons that generate anxiety. Material and Method . The study included 81 cancer patients submitted to the 18 F-FDG PET/CT low dose scan. Patients filled in the Scan Experience Questionnaire and the State-Trait Anxiety Inventory (STAI) before and after 18 F-FDG PET/CT low dose scan. Results . Substantial levels of anxiety were detected both before and after 18 F-FDG PET/CT low dose scan (STAI mean > 30), with a significant increase in the state of anxiety after scan performance (p < 0.0001, M e d i a n p r e = 31.1, andM e d i a n p o s = 33.0). 18 F-FDG PET/CT low dose results are the main cause of anxiety both before (79.1%) and after (86.9%) the scan. The information provided by staff both before and on the 18 F-FDG PET/CT low dose day was classified mostly as completely understandable (70.5% and 75.3%, resp.) and as very useful (70.5% and 72.6%, resp.) and correlated positively with patients' overall satisfaction with NM Department (r S = 0.372, p = 0.004 andr S = 0.528, p = 0.000, resp.), but not with anxiety levels. Conclusions . Patients perceive high levels of anxiety during the 18 F-FDG PET/CT low dose scan and the concern with scan results was pointed out as the main factor for that emotional reaction.